Вибір адсорбенту для очистки скидних газів содового виробництва від сірководню - Зінченко, Марія Георгіївна; Цейтлін, Мусій Абрамович (Національний університет "Львівська політехніка", 2018)
The comparison of adsorbents, which allow purification of waste gases of soda ash production from hydrogen sulfide, was made. The following adsorbents were investigated: zeolite Ca A, silica gel of the KSMG and ShSMG grades, as well as activated charcoal of grades AR-B. The comparison was made on the time of the protective action. The best result is obtained with the application of activated carbon. The zeolite and silica gel of the SHSMG brand is approximately the same, but 2.5 times worse than that of activated carbon. The protective action time of the zeolite of the KSMG brand is 5 times smaller than that of coal.
Keywords: адсорбенти; оксид вуглецю; сірководень; адсорбційні установки; очищення газів; содове виробництво